Solar cell and preparation method and application thereof
By setting a groove structure with a smaller density on the backlight surface of the solar cell and optimizing the suede density, the problems of uneven filling and bubble gaps in the back passivation effect of traditional solar cells are solved, and more efficient battery performance and reliability are achieved.
Patent Information
- Application Number
- CN202510020349.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-25
AI Technical Summary
During the process of improving the back passivation effect of traditional solar cells, the suede structure leads to uneven filling, bubble gaps, increased light-shielding area and improved contact resistance, affecting battery efficiency and reliability.
A solar cell is designed, with a stacked structure and a negative electrode gate line on the backlight surface, and a groove structure with a smaller density is provided on the backlight surface. The negative electrode gate line is arranged in the groove to jointly optimize the suede density of the backlight surface and the light-receiving surface.
By improving the trapping effect, reducing short-circuit current loss and contact resistance, improving gate line adhesion and filling factor, the efficiency and reliability of solar cells are significantly improved.
Smart Images

Figure CN119894162A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a solar cell and a preparation method and application thereof. Background Art
[0002] Traditional solar cells focus on improving efficiency on the front side, and usually use a single-polishing process to reduce the specific surface area of the back side of the cell, thereby reducing the recombination of minority carriers, increasing the open circuit voltage, and improving the efficiency of the cell. However, in fact, improving the passivation effect on the back side of the solar cell is also the key to improving efficiency.
[0003] However, although the conventional suede structure is beneficial to improving the passivation effect on the back side, it will also cause other problems: on the one hand, the suede structure on the back side will affect the filling of the screen slurry, resulting in gaps and bubbles during the filling process, thereby affecting the adhesion and tension of the grid line and reducing the reliability of the battery; on the other hand, the suede structure on the back side will not only affect the shading area of the grid line, causing short-circuit current loss, but also affect the contact between the grid line and the surface, resulting in an increase in contact resistance, thereby affecting the battery efficiency. Summary of the invention
[0004] Based on this, it is necessary to provide a solar cell and a preparation method and application thereof to address the above problems; the solar cell can not only achieve maximum efficiency but also has excellent reliability.
[0005] A solar cell comprises a silicon substrate, wherein the silicon substrate has a light-receiving surface and a backlight surface arranged opposite to each other, wherein the surface of the backlight surface comprises a laminated structure and a negative electrode grid line arranged on the surface of the laminated structure;
[0006] The backlight surface includes at least one groove, and the negative pole grid line is arranged in the groove, the inner wall of the groove is formed with a first velvet surface, and the light receiving surface is formed with a second velvet surface, and the density of the first velvet surface per unit area is less than the density of the second velvet surface.
[0007] In one embodiment, a density ratio of the first suede surface to the second suede surface is greater than or equal to 1:3.
[0008] In one embodiment, the density of the first velvet surface is 1×10 5 / mm 2 -2×10 5 / mm 2 ;
[0009] And / or, the density of the second suede surface is 2.5×10 5 / mm 2 -3×10 5 / mm 2 .
[0010] In one embodiment, the height of any pyramid in the first velvet surface is 0.1 μm-1 μm, and the length of the base is 3 μm-10 μm;
[0011] And / or, the height of any pyramid in the second velvet surface is 0.8 μm-1.5 μm, and the length of the base is 0.1 μm-2 μm.
[0012] In one embodiment, the volume ratio of any pyramid in the first velvet surface to any pyramid in the second velvet surface is 4:1-6:1.
[0013] In one of the embodiments, the negative electrode grid line fills the groove.
[0014] In one embodiment, the groove has a depth of 6 μm-10 μm and a width of 16 μm-20 μm.
[0015] A method for preparing the solar cell as described above comprises the following steps:
[0016] Providing a silicon substrate, the silicon substrate comprising a first surface and a second surface arranged opposite to each other;
[0017] Performing a first wet texturing on the first surface by using a local mask to form a groove structure whose inner wall is a first velvet surface;
[0018] Performing a second wet texturing on the second surface using a mask to form the second texturing surface, wherein the concentration of the texturing additive in the texturing liquid of the first wet texturing is less than the concentration of the texturing additive in the texturing liquid of the second wet texturing;
[0019] The laminated structure and the grid line are respectively prepared on the first surface and the second surface after the texturing to obtain the solar cell.
[0020] In one embodiment, the concentration of the texturing additive in the texturing liquid of the first wet texturing is 0.1%-3%;
[0021] And / or, the concentration of the texturing additive in the texturing liquid of the second wet texturing is 0.2%-4%;
[0022] And / or, the temperature of the first wet texturing is greater than the temperature of the second wet texturing;
[0023] And / or, the time of the first wet texturing is greater than the time of the second wet texturing.
[0024] A photovoltaic module comprises the solar cell described above.
[0025] The solar cell described in the present invention has a special backlight surface structure design, and synergistically optimizes the velvet density of the backlight surface and the light-receiving surface. On the one hand, it is not only beneficial to improve the light trapping effect, but also beneficial to reduce the shading area of the grid line, thereby reducing the short-circuit current loss, while improving the contact between the grid line and the surface, thereby reducing the contact resistance, and thus effectively improving the battery efficiency; on the other hand, the groove structure in the backlight surface is beneficial to the filling of the slurry, which can not only increase the contact area between the grid line and the laminated structure, improve the filling factor of the solar cell and the welding tension of the grid line, so that the adhesion tension of the grid line is greatly improved, but also can avoid the appearance of bubbles and gaps in the slurry during the filling process, thereby improving the adhesion of the slurry to the semiconductor substrate layer, and thus increasing the reliability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 FIG. 4 is a schematic diagram of the cross-sectional structure of a solar cell in one embodiment of the present invention.
[0028] Among them, 101 is a silicon substrate; 102 is a first intrinsic amorphous silicon layer; 103 is a first doped layer; 104 is a first transparent conductive film layer; 105 is a negative electrode grid line; 106 is a second intrinsic amorphous silicon layer; 107 is a second doped layer; 108 is a second transparent conductive film layer; 109 is a positive electrode grid line. DETAILED DESCRIPTION
[0029] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0031] The present invention provides a solar cell, including but not limited to a heterojunction cell, a TOPCon cell, a PERC cell, etc. Specifically, Figure 1 As shown, a cross-sectional structure of a heterojunction battery provided by the present invention includes a silicon substrate 101, wherein the silicon substrate 101 has a light-receiving surface and a backlight surface arranged opposite to each other, and the surface of the backlight surface includes a stacked structure and a negative electrode grid line 105 arranged on the surface of the stacked structure, wherein the stacked structure may include a first intrinsic amorphous silicon layer 102, a first doped layer 103, a first transparent conductive film layer 104 and a negative electrode grid line 105 stacked in sequence. It can be understood that the present invention is also applicable to stacked structures of other batteries.
[0032] The backlight surface includes at least one groove, and the negative pole grid line 105 is arranged in the groove, the inner wall of the groove is formed with a first velvet surface, and the light receiving surface is formed with a second velvet surface, and the density of the first velvet surface per unit area is less than the density of the second velvet surface.
[0033] The solar cell described in the present invention arranges a groove structure with a lower velvet density on the backlight surface, so that the negative electrode grid line 105 is arranged in the groove, and the velvet density of the light-receiving surface is arranged to be larger. On the one hand, it is not only beneficial to improve the light trapping effect, but also beneficial to reduce the shading area of the grid line, thereby reducing the short-circuit current loss, and at the same time improves the contact between the grid line and the surface, thereby reducing the contact resistance, and then effectively improving the battery efficiency.
[0034] On the other hand, the groove structure in the backlight surface is conducive to the filling of the slurry, which can not only increase the contact area between the grid line and the stacked structure, improve the filling factor of the solar cell and the welding tension of the grid line, greatly improve the adhesion tension of the grid line, but also avoid the appearance of bubbles and gaps in the slurry during the filling process, thereby improving the adhesion of the slurry to the semiconductor substrate layer, and then increasing the reliability of the battery.
[0035] It is understandable that the present invention does not limit the number of grooves, which can be one or two or more, and can be designed according to actual preparation requirements. The inner wall of the groove is also attached with a partial laminated structure, but the groove is not completely filled, so that the negative electrode grid line 105 can be arranged in the groove.
[0036] It should be noted that the velvet surface is composed of a single velvet structure arranged in an array, and the density of the velvet surface indicates the amount of velvet produced per unit area, that is, the number of single velvet structures per unit area. For example, when the single velvet structure is a pyramid, the density of the velvet surface can be obtained by testing the number of points of the pyramid per unit area. The greater the amount of velvet produced per unit area, the greater the density of the velvet surface, and the smaller the area occupied by the single velvet structure on the velvet surface under the same area. Therefore, the density of the first velvet surface per unit area is less than the density of the second velvet surface, indicating that under the same area, the amount of velvet produced by the first velvet surface is less than the amount of velvet produced by the second velvet surface, and the area occupied by the single velvet structure on the velvet surface in the first velvet surface is greater than the area occupied by the single velvet structure on the velvet surface in the second velvet surface. Furthermore, when the height of the single velvet structure in the first velvet surface is the same as that of the single velvet structure in the second velvet surface, the volume size of the single velvet structure in the first velvet surface is larger, while the volume size of the single velvet structure in the second velvet surface is smaller.
[0037] Preferably, the density ratio of the first velvet surface to the second velvet surface is greater than or equal to 1:3, which further synergistically optimizes the velvet density of the backlight surface and the light-receiving surface, which is beneficial to further enhance the light trapping effect and thus significantly improve the battery efficiency.
[0038] Specifically, a density ratio of the first suede surface to the second suede surface includes but is not limited to any point value among 1:3, 1:2.5, 1:2, 1:1.5, 1:1.25 or a range value between any two of them.
[0039] More preferably, the density of the first velvet surface is 1×10 5 / mm 2 -2×10 5 / mm 2 , including but not limited to 1×10 5 / mm 2 , 1.2×10 5 / mm 2 , 1.5×10 5 / mm 2 , 1.6×10 5 / mm 2 , 1.8×10 5 / mm 2 , 2×10 5 / mm 2 Any point value in or any range of values between them.
[0040] More preferably, the density of the second suede surface is 2.5×10 5 / mm 2 -3×10 5 / mm 2 , including but not limited to 2.5×10 5 / mm 2 , 2.6×10 5 / mm 2 , 2.7×10 5 / mm 2 , 2.8×10 5 / mm 2 , 2.9×10 5 / mm 2 , 3×10 5 / mm 2 Any point value in or any range of values between them.
[0041] It should be noted that the present invention does not limit the shape of a single pile structure in the pile surface, including but not limited to a pyramid or other irregular three-dimensional shapes. Preferably, the pile surface structure is composed of a pyramid.
[0042] In one embodiment of the present invention, when the structure of the first velvet surface is selected from a pyramid, the height of any pyramid in the first velvet surface is preferably 0.1μm-1μm, including but not limited to any point value among 0.1μm, 0.2μm, 0.5μm, 0.8μm, 1μm or a range value between any two of them; the length of the base is preferably 3μm-10μm, including but not limited to any point value among 3μm, 4μm, 5μm, 6μm, 8μm, 10μm or a range value between any two of them.
[0043] In one embodiment of the present invention, when the structure of the second velvet is selected from pyramids, the height of any pyramid in the second velvet is preferably 0.8μm-1.5μm, including but not limited to any point value among 0.8μm, 1μm, 1.2μm, 1.5μm or any range value between two of them; the length of the base is preferably 0.1μm-2μm, including but not limited to any point value among 0.1μm, 0.5μm, 1μm, 1.5μm, 2μm or any range value between two of them.
[0044] Preferably, the structures of the first velvet surface and the second velvet surface are both selected from pyramids, wherein the height of any pyramid in the first velvet surface is 0.1μm-1μm, and the base length is 3μm-10μm, and the height of any pyramid in the second velvet surface is 0.8μm-1.5μm, and the base length is 0.1μm-2μm.
[0045] In one embodiment of the present invention, the volume ratio of any pyramid in the first velvet surface to any pyramid in the second velvet surface is 4:1-6:1, including but not limited to any point value of 4:1, 4.5:1, 5:1, 5.5:1, 6:1 or a range value between any two of them.
[0046] In the present invention, the negative electrode grid line 105 is arranged in the groove. In other words, the present invention only limits the positional relationship between the negative electrode grid line 105 and the groove, and does not limit the size relationship between the negative electrode grid line 105 and the groove. Preferably, the negative electrode grid line 105 fills the groove, that is, the length and width of the negative electrode grid line 105 are equal to the length and width of the groove, ensuring that the negative electrode grid line 105 is in full contact with the groove, so that the suede structure is better connected to the grid line, which is conducive to further improving the efficiency.
[0047] It can be understood that before the negative electrode grid line 105 is prepared, part of the laminated structure has been attached to the inner wall of the groove, and the negative electrode grid line 105 fills the groove after the laminated structure is attached.
[0048] Considering that if the longitudinal height of the negative electrode grid line 105 is significantly different from the groove depth, it may affect the shading effect of the other side of the grid line, which is not conducive to light absorption and thus reduces efficiency, it is preferred that the longitudinal height of the negative electrode grid line is at least equal to the groove depth, and it is further preferred that the length, width, and height of the negative electrode grid line 105 are the same as the length, width, and height of the groove after the laminate structure is attached.
[0049] In one embodiment of the present invention, the depth of the groove is 6μm-10μm, including but not limited to any point value among 6μm, 7μm, 8μm, 9μm, 10μm or any range value between two of them; the width is 16μm-20μm, including but not limited to any point value among 16μm, 17μm, 18μm, 19μm, 20μm or any range value between two of them.
[0050] Combination Figure 1 As shown, in the heterojunction battery provided by the present invention, the surface of the light-receiving surface also includes a stacked structure. Specifically, the stacked structure of the light-receiving surface includes a second intrinsic amorphous silicon layer 106, a second doped layer 107, a second transparent conductive film layer 108 and a positive electrode grid line 109 which are stacked in sequence.
[0051] It should be noted that the present invention does not limit the materials and sizes of the first intrinsic amorphous silicon layer 102, the first doped layer 103, the first transparent conductive film layer 104, the negative electrode grid line 105, the second intrinsic amorphous silicon layer 106, the second doped layer 107, the second transparent conductive film layer 108, and the positive electrode grid line 109, and the conventional materials and sizes in the art can be used. Among them, the materials and sizes of the first intrinsic amorphous silicon layer 102 and the second intrinsic amorphous silicon layer 106 can be the same or different; the materials and sizes of the first doped layer 103 and the second doped layer 107 can be the same or different; the materials and sizes of the first transparent conductive film layer 104 and the second transparent conductive film layer 108 can be the same or different; the materials and sizes of the negative electrode grid line 105 and the positive electrode grid line 109 can be the same or different, and the present invention does not limit this.
[0052] The present invention provides a method for preparing the solar cell as described above, comprising the following steps:
[0053] S1, providing a silicon substrate, wherein the silicon substrate comprises a first surface and a second surface arranged opposite to each other;
[0054] S2, performing a first wet texturing on the first surface using a local mask to form a groove structure whose inner wall is a first velvet surface;
[0055] S3, performing a second wet texturing on the second surface using a mask to form the second texturing surface, wherein the concentration of the texturing additive in the texturing liquid of the first wet texturing is less than the concentration of the texturing additive in the texturing liquid of the second wet texturing;
[0056] S4, preparing a laminated structure and a grid line on the first surface and the second surface after texturing, respectively, to obtain the solar cell.
[0057] It should be noted that the present invention does not limit the preparation order of step S2 and step S3. Step S2 may be performed first, and then step S3; or step S3 may be performed first, and then step S2.
[0058] In step S1 to step S3, the first surface is locally etched using a local mask, and at the same time, the concentrations of the texturing additives in the texturing liquids of the first and second surfaces are coordinated and controlled, differentiated structural designs are performed on the first and second surfaces, and the texturing density of the first and second surfaces is optimized, so that the efficiency of the solar cell produced is maximized and has excellent reliability.
[0059] In one embodiment of the present invention, the concentration of the texturing additive in the texturing liquid of the first wet texturing is 0.1%-3%, including but not limited to any point value among 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or any range value between two of them.
[0060] In one embodiment of the present invention, the concentration of the texturing additive in the texturing liquid of the second wet texturing is 0.2%-4%, including but not limited to any point value among 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4% or any range value between two of them.
[0061] In one embodiment of the present invention, the texturing liquids of the first wet texturing and the second wet texturing are independently selected from a mixture of an alkali solution and a texturing additive.
[0062] Specifically, the alkali solution is selected from potassium hydroxide solution, sodium hydroxide solution or a mixture of potassium hydroxide and sodium hydroxide, and the concentration of the solute in the alkali solution is preferably 1.2%-1.3%.
[0063] Specifically, the texturing additive includes 1.0wt%-2.0wt% of potassium sorbate, 2.0wt%-4.0wt% of sodium acetate, 5.0wt%-7.0wt% of a defoaming agent, 5.0wt%-10.0wt% of a surfactant and the balance of water.
[0064] In one embodiment of the present invention, the temperature of the first wet texturing process is greater than the temperature of the second wet texturing process, which is beneficial for further precise control of the texture structure and density of the first surface and the second surface.
[0065] Preferably, the temperature of the first wet texturing process is 82°C-85°C, including but not limited to any point value among 82°C, 83°C, 84°C, 85°C or any range value between two of them; the temperature of the second wet texturing process is 80°C-82°C, including but not limited to any point value among 80°C, 81°C, 82 or any range value between two of them.
[0066] In one embodiment of the present invention, the time of the first wet texturing is longer than the time of the second wet texturing, which is beneficial to further accurately control the texture structure and density of the first surface and the second surface.
[0067] Preferably, the time for the first wet texturing is 450s-500s, including but not limited to any point value among 450s, 460s, 470s, 480s, 490s, 500s or any range value between two of them; the time for the second wet texturing is 400s-480s, including but not limited to any point value among 400s, 420s, 450s, 460s, 480s or any range value between two of them.
[0068] It can be understood that the mask process used in the present invention is a conventional technology in the field, for example: partially coating the surface of the silicon wafer with a photosensitive material by rolling, spraying, spin coating, immersion, screen printing, etc. to form a mask, the mask is a wet film, which is a photosensitive ink, and its main components include resin, active diluent, photoinitiator and additives, etc.; the mask is exposed to ultraviolet light, and the photoinitiator in the mask absorbs light energy under the excitation of ultraviolet light to become free radicals, and the monomer produces a cross-linking reaction under the addition of free radicals to form a polymer and solidify. After the texturing is completed, the solidified mask is removed by wet etching. Specifically, an acidic degumming solution is used to remove the solidified mask, wherein the acidic degumming solution is selected from a mixture of concentrated sulfuric acid and hydrogen peroxide. When sulfuric acid and hydrogen peroxide are used in combination, strong oxidizing hydrogen sulfate and hydroxyl radicals are generated, which can oxidize the organic matter in the photoresist and convert it into a low-molecular weight compound that is more soluble in water. In addition, the hydroxyl radicals can also induce the breakage of the photoresist polymer chain, thereby reducing its molecular weight and removing the solidified mask.
[0069] It should be noted that the present invention does not limit the process for preparing the stacked structure and the gate line in step S4, and conventional processes can be used.
[0070] The present invention also provides a photovoltaic module, comprising the solar cell described above. The photovoltaic module can be widely used in multiple fields such as power generation, outdoor lighting, mobile power supply, and aerospace, and the present invention does not limit this.
[0071] The solar cell and its preparation method and application will be further described below through the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0072] Example 1
[0073] The first surface of the silicon wafer is completely coated with a photosensitive material by spin coating to form a mask, and the mask is exposed and cured by ultraviolet light. 4L of 45% alkali solution (KOH / NaOH), 1.2L of texturing additives and the rest of water are added to a 500L tank as texturing liquid, wherein the concentration of the texturing additive in the texturing liquid is 0.24%, and the texturing additive includes 1.5wt% potassium sorbate, 3wt% sodium acetate, 6wt% defoaming agent, 80wt% surfactant and the rest of water. The second surface not covered with the mask is wet-textured at 82°C for 450s using the texturing liquid to form a second velvet surface.
[0074] The cured mask on the first surface is removed by wet etching, and a photosensitive material is applied to a part of the first surface and the second surface after texturing by spin coating, and the mask is exposed and cured by ultraviolet light. 4L of 45% alkali solution (KOH / NaOH), 1L of texturing additive and the rest of water are added to a 500L tank as texturing liquid, wherein the concentration of the texturing additive in the texturing liquid is 0.2%, and the texturing additive includes 1.5wt% potassium sorbate, 3wt% sodium acetate, 6wt% defoaming agent, 80wt% surfactant and the rest of water. The part of the first surface not covered by the mask is wet-textured for 460s at 82°C using the texturing liquid to form a groove structure with the inner wall being the first velvet surface.
[0075] A wet etching method is used to remove part of the first surface and the solidified mask of the second surface after texturing. CVD deposition is performed on the first and second surfaces after texturing to form an intrinsic amorphous silicon film layer and a doped microcrystalline silicon film layer. Then PVD deposition is performed to form a transparent conductive thin film layer. Finally, screen-printed gate line electrodes are used to obtain a heterojunction battery.
[0076] Example 2
[0077] The first surface of the silicon wafer is completely coated with a photosensitive material by spin coating to form a mask, and the mask is exposed and cured by ultraviolet light. 4L of 45% alkali solution (KOH / NaOH), 1.3L of texturing additives and the rest of water are added to a 500L tank as texturing liquid, wherein the concentration of the texturing additive in the texturing liquid is 0.26%, and the texturing additive includes 1.5wt% potassium sorbate, 3wt% sodium acetate, 6wt% defoaming agent, 80wt% surfactant and the rest of water. The second surface not covered with the mask is wet-textured at 82°C for 460s using the texturing liquid to form a second velvet surface.
[0078] The cured mask on the first surface is removed by wet etching, and a photosensitive material is applied to a part of the first surface and the second surface after texturing by spin coating, and the mask is exposed and cured by ultraviolet light. 4L of 45% alkali solution (KOH / NaOH), 1.1L of texturing additive and the rest of water are added to a 500L tank as texturing liquid, wherein the concentration of the texturing additive in the texturing liquid is 0.22%, and the texturing additive includes 1.5wt% of potassium sorbate, 3wt% of sodium acetate, 6wt% of defoaming agent, 80wt% of surfactant and the rest of water. The part of the first surface not covered by the mask is wet texturing for 470s at 84°C using the texturing liquid to form a groove structure with the inner wall being the first velvet surface.
[0079] A wet etching method is used to remove part of the first surface and the solidified mask of the second surface after texturing. CVD deposition is performed on the first and second surfaces after texturing to form an intrinsic amorphous silicon film layer and a doped microcrystalline silicon film layer. Then PVD deposition is performed to form a transparent conductive thin film layer. Finally, screen-printed gate line electrodes are used to obtain a heterojunction battery.
[0080] Example 3
[0081] The first surface of the silicon wafer is completely coated with a photosensitive material by spin coating to form a mask, and the mask is exposed and cured by ultraviolet light. 4L of 45% alkali solution (KOH / NaOH), 1.4L of texturing additives and the rest of water are added to a 500L tank as texturing liquid, wherein the concentration of the texturing additive in the texturing liquid is 0.28%, and the texturing additive includes 1.5wt% potassium sorbate, 3wt% sodium acetate, 6wt% defoaming agent, 80wt% surfactant and the rest of water. The second surface not covered with the mask is wet-textured at 82°C for 470s using the texturing liquid to form a second velvet surface.
[0082] The cured mask on the first surface is removed by wet etching, and a photosensitive material is applied to a part of the first surface and the second surface after texturing by spin coating, and the mask is exposed and cured by ultraviolet light. 4L of 45% alkali solution (KOH / NaOH), 1.2L of texturing additives and the rest of water are added to a 500L tank as texturing liquid, wherein the concentration of the texturing additive in the texturing liquid is 0.24%, and the texturing additive includes 1.5wt% potassium sorbate, 3wt% sodium acetate, 6wt% defoaming agent, 80wt% surfactant and the rest of water. The part of the first surface not covered by the mask is wet texturing for 480s at 84°C using the texturing liquid to form a groove structure with the inner wall being the first velvet surface.
[0083] A wet etching method is used to remove part of the first surface and the solidified mask of the second surface after texturing. CVD deposition is performed on the first and second surfaces after texturing to form an intrinsic amorphous silicon film layer and a doped microcrystalline silicon film layer. Then PVD deposition is performed to form a transparent conductive thin film layer. Finally, screen-printed gate line electrodes are used to obtain a heterojunction battery.
[0084] Example 4
[0085] The first surface of the silicon wafer is completely coated with a photosensitive material by spin coating to form a mask, and the mask is exposed and cured by ultraviolet light. 4L of 45% alkali solution (KOH / NaOH), 1.5L of texturing additives and the rest of water are added to a 500L tank as texturing liquid, wherein the concentration of the texturing additive in the texturing liquid is 0.3%, and the texturing additive includes 1.5wt% potassium sorbate, 3wt% sodium acetate, 6wt% defoaming agent, 80wt% surfactant and the rest of water. The second surface not covered with the mask is wet-textured at 84°C for 480s using the texturing liquid to form a second velvet surface.
[0086] The cured mask on the first surface is removed by wet etching, and a photosensitive material is applied to a part of the first surface and the second surface after texturing by spin coating, and the mask is exposed and cured by ultraviolet light. 4L of 45% alkali solution (KOH / NaOH), 1.3L of texturing additives and the rest of water are added to a 500L tank as texturing liquid, wherein the concentration of the texturing additive in the texturing liquid is 0.26%, and the texturing additives include 1.5wt% potassium sorbate, 3wt% sodium acetate, 6wt% defoaming agent, 80wt% surfactant and the rest of water. The part of the first surface not covered by the mask is wet texturing for 480s at 85°C using the texturing liquid to form a groove structure with the inner wall being the first velvet surface.
[0087] A wet etching method is used to remove part of the first surface and the solidified mask of the second surface after texturing. CVD deposition is performed on the first and second surfaces after texturing to form an intrinsic amorphous silicon film layer and a doped microcrystalline silicon film layer. Then PVD deposition is performed to form a transparent conductive thin film layer. Finally, screen-printed gate line electrodes are used to obtain a heterojunction battery.
[0088] Example 5
[0089] The first surface of the silicon wafer is completely coated with a photosensitive material by spin coating to form a mask, and the mask is exposed and cured by ultraviolet light. 4L of 45% alkali solution (KOH / NaOH), 1.3L of texturing additives and the rest of water are added to a 500L tank as texturing liquid, wherein the texturing additives in the texturing liquid include 15wt% potassium sorbate, 3wt% sodium acetate, 6wt% defoaming agent, 80wt% surfactant and the rest of water. The second surface not covered with the mask is wet-textured at 82°C for 450s using the texturing liquid to form a second velvet surface.
[0090] The cured mask on the first surface is removed by wet etching, and a photosensitive material is applied to a part of the first surface and the second surface after texturing by spin coating, and the mask is exposed and cured by ultraviolet light. 4L of 45% alkali solution (KOH / NaOH), 1L of texturing additive and the rest of water are added to a 500L tank as texturing liquid, wherein the texturing additive in the texturing liquid includes 15wt% potassium sorbate, 3wt% sodium acetate, 6wt% defoaming agent, 80wt% surfactant and the rest of water. The part of the first surface not covered by the mask is wet-textured at 84°C for 480s using the texturing liquid to form a groove structure with the inner wall being the first velvet surface.
[0091] The silicon wafer is diffused, routinely cleaned twice, and an aluminum oxide / silicon nitride stacked passivation film is deposited on the back. It is then laser grooved, screen printed, and sintered to obtain a PERC cell with a polished back side.
[0092] Comparative Example 1
[0093] The difference between Comparative Example 1 and Example 1 is that the first velvet surface is prepared by using the same velvet-making liquid as that used to prepare the second velvet surface.
[0094] Comparative Example 2
[0095] The difference between Comparative Example 2 and Example 1 is that the second velvet surface is prepared by using the same velvet-making liquid as that used to prepare the first velvet surface.
[0096] Comparative Example 3
[0097] The difference between Comparative Example 3 and Example 5 is that the second velvet surface is prepared by using the same velvet-making liquid as that used to prepare the first velvet surface.
[0098] The velvet structures obtained in Examples 1-5 and Comparative Examples 1-3 were tested, and the results are shown in Table 1. It should be noted that the velvet structures obtained above are all regular quadrangular pyramids.
[0099] Table 1
[0100]
[0101] The solar cells prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to performance tests, and the results are shown in Table 2. The efficiency test method is: Photovoltaic Conversion Efficiency (PCE) test; The reliability test method is: (1) UV test: The irradiation amount is 6 KWh / m 2 , power 20W, time 99min, temperature 60±2℃, connection method short circuit, standard test result UV<2.034%; (2) LID test: total irradiation 5KWh / m 2, temperature: 60±10℃, time 5h, standard test result LID<0.6%; (3) Tensile test: 3M tape completely adheres to the grid line, the pulling direction is 180 degrees opposite to the printed surface, and the position of each battery cell is selected from the front and back sides. The judgment standard: a small amount of residual slurry is allowed on the tape, the single point detachment length is ≤3mm and there is no broken grid in the EL test, which is qualified; 3 consecutive points are unqualified or 6 discontinuous unqualified points are judged as unqualified.
[0102] Table 2
[0103] PCE(%) UV(%) LID(%) pull Example 1 25.89 1.25 0.40 qualified Example 2 25.94 1.12 0.16 qualified Example 3 25.91 1.33 0.23 qualified Example 4 25.93 1.20 0.25 qualified Example 5 20.99 1.10 0.37 qualified Comparative Example 1 25.75 1.50 0.065 qualified Comparative Example 2 25.80 1.45 0.05 qualified Comparative Example 3 20.32 1.33 0.27 qualified
[0104] It can be seen from Table 1 and Table 2 that the solar cell provided by the present invention can not only achieve maximum efficiency but also has excellent reliability.
[0105] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0106] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A solar cell, characterized in that: The invention comprises a silicon substrate, wherein the silicon substrate has a light-receiving surface and a backlight surface which are arranged opposite to each other, and the surface of the backlight surface comprises a laminated structure and a negative electrode grid line arranged on the surface of the laminated structure; The backlight surface includes at least one groove, and the negative pole grid line is arranged in the groove, the inner wall of the groove is formed with a first velvet surface, and the light receiving surface is formed with a second velvet surface, and the density of the first velvet surface per unit area is less than the density of the second velvet surface.
2. The solar cell according to claim 1, characterized in that A density ratio of the first suede surface to the second suede surface is greater than or equal to 1:
3.
3. The solar cell according to claim 1 or 2, characterized in that: The density of the first velvet surface is 1×10 5 / mm 2 -2×10 5 / mm 2 ; And / or, the density of the second suede surface is 2.5×10 5 / mm 2 -3×10 5 / mm 2 .
4. The solar cell according to claim 1, characterized in that The height of any pyramid in the first velvet surface is 0.1 μm-1 μm, and the length of the base is 3 μm-10 μm; And / or, the height of any pyramid in the second velvet surface is 0.8 μm-1.5 μm, and the length of the base is 0.1 μm-2 μm.
5. The solar cell according to claim 4, characterized in that: The volume ratio of any pyramid in the first velvet surface to any pyramid in the second velvet surface is 4:1-6:
1.
6. The solar cell according to claim 1, characterized in that The negative electrode grid line fills the groove.
7. The solar cell according to claim 1 or 6, characterized in that: The groove has a depth of 6 μm-10 μm and a width of 16 μm-20 μm.
8. A method for preparing a solar cell according to any one of claims 1 to 7, characterized in that: The steps include: Providing a silicon substrate, the silicon substrate comprising a first surface and a second surface arranged opposite to each other; Performing a first wet texturing on the first surface by using a local mask to form a groove structure whose inner wall is a first velvet surface; Performing a second wet texturing on the second surface using a mask to form the second texturing surface, wherein the concentration of the texturing additive in the texturing liquid of the first wet texturing is less than the concentration of the texturing additive in the texturing liquid of the second wet texturing; The laminated structure and the grid line are respectively prepared on the first surface and the second surface after the texturing to obtain the solar cell.
9. The method for preparing a solar cell according to claim 8, characterized in that: The concentration of the texturing additive in the texturing liquid of the first wet texturing is 0.1%-3%; And / or, the concentration of the texturing additive in the texturing liquid of the second wet texturing is 0.2%-4%; And / or, the temperature of the first wet texturing is greater than the temperature of the second wet texturing; And / or, the time of the first wet texturing is greater than the time of the second wet texturing.
10. A photovoltaic module, characterized in that: The invention comprises a solar cell as claimed in any one of claims 1 to 7.
Citation Information
Cited By
Solar cell, manufacturing method thereof and photovoltaic module
CN120076496A
Solar cell, method of manufacturing the same, and photovoltaic module
CN120076496B
Back contact solar cell and cell assembly
CN120568930A